Pengaruh Capital TurnOver, Return on Equity, dan Firm Size terhadap Price Book Value - Aemelia Angesti; Fernaldy Fernaldy; Maisarah Maisarah; Erica Erica; Desy Anwar; Wenny Anggeresia Ginting; Mohd. Nawi Nawi Purba (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
This study’s main objective is to examine the effect of working capital turnover, return on equity, and firm size toward price book value in the manufacturing companies listed on the Indonesian Stock Exchange in 2013-2016. Working capital turnover is the proxy chosen from activity ratio. Return on equity is the proxy chosen from probability ratio. Firm size is based on total assets, with the nominal itself is in natural logarithms. Sample of research was determined by purposive sampling method to obtain 58 manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the years 2013-2016. This study uses secondary data. Validity test of this study is done with multiple regression analysis and classic assumption test. The results of this study indicates that there is significant influence between the variables Working Capital Turnover, Return on Equity, and Firm Size toward Price Book Value.